(untitled) (Advances in Applied Mathematics and Mechanics, 2018)
In this paper, a hybrid dynamic mesh generation method for multi-block structured grid is presented based on inverse distance weighting (IDW) interpolation and transfinite interpolation (TFI). The major advantage of the algorithm is that it maintains the effectiveness of TFI, while possessing the ability to deal with multi-block structured grid from the IDW method. In this approach, dynamic mesh generation is made in two steps. At first, all domain vertexes with known deformation are selected as sample points and IDW interpolation is applied to get the grid deformation on domain edges. Then, an arc-length-based TFI is employed to efficiently calculate the grid deformation on block faces and inside each block. The present approach can be well applied to both two-dimensional (2D) and three-dimensional (3D) problems. The proposed method has been well-validated by several test cases. Numerical results show that dynamic meshes with high quality can be generated in an accurate and efficient manner.